HLA-DR17 and Mooren's ulcer in South India. Issue 2 (22nd January 2008) - Zelefsky, J R; Taylor, C J; Srinivasan, M; Peacock, S; Goodman, R S; Key, T; Watson, P G; Cunningham, E T
Abstract : Objective: To investigate the association between Mooren's ulcer and human leucocyte antigen (HLA) type DR17(3) in patients from the Tamil Nadu State of South India. Methods: Blood samples from 38 patients with Mooren's ulcer and 45 age- and sex-matched controls were obtained prospectively. HLA-DR and HLA-DQ typing was performed by PCR using sequence-specific primers. Results: Fifteen (40%) of the patients with Mooren's ulcer tested positive for HLA-DR17(3) compared with seven (16%) of the controls (p = 0.01). Seventeen (45%) of the patients also tested positive for the closely linked HLA-DQ2 compared with 11 (24%) of controls (p = 0.05). When adjusted for multiplicity, the correlation between HLA-DR17(3) and Mooren's ulcer remained significant (p = 0.03). Conclusions: These data demonstrate an association between HLA-DR17(3) and Mooren's ulcer in South Indian patients, supporting autoimmune theories about the pathogenesis of the disorder.